Developing a Simple and Feasible Process for the Crude Extraction of Livetins and Phosvitin from Egg Yolk - Fan Zhang; Yongmei Ding; Zipei Zhang; Hangxin Zhu; Han Jiao; Shijian Dong; Junhua Li; Luping Gu; Cuihua Chang; Yanjun Yang; Yujie Su (Foods)
Due to imbalanced demand favoring egg whites, the egg industry faces a surplus of egg yolk, limiting overall growth. This study designed a feasible process for the crude extraction of livetins and phosvitin (PV) and revealed the related separation mechanisms. Our method utilized a 1:9 egg yolk dilution at pH 6.15–6.29, incubated at 4–7.5 °C, to reduce the dispersibility of lipoproteins in the water-soluble fraction (WSF). Adding 0.04–0.05% (w/v) sodium alginate to WSF at pH 5.40 effectively removed suspended low-density lipoprotein (LDL) through electrostatic complexation, increasing livetins electrophoretic bands from 51.90% to 91.04%. The dispersion of the high-density lipoprotein (HDL)-PV complex was jointly affected by NaCl and pH, with phosphocalcic bridges fully disrupted when NaCl concentration exceeded 7.5% (w/v). Na+ and Ca2+ were adsorbed onto the negatively charged protein surface at pH 5–8, inducing strong hydration repulsion, thereby resulting in the individual dispersion of HDL and PV. Based on the solubility difference in low ionic strength solutions at neutral pH, HDL could be effectively removed after dialysis, increasing PV electrophoretic bands from 8.45% to 61.50%. This simple and feasible separation process may provide a reliable foundation for further purification via membrane filtration and chromatography.